2017
DOI: 10.1016/j.jpor.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of IL-1 gene polymorphisms ( IL1A , IL1B , and IL1RN ) as a risk factor in unsuccessful implants retaining overdentures

Abstract: The prediction model developed in this study could serve as a basis for further improved models that would assist clinicians in the daily diagnosis and treatment planning practice of oral rehabilitation with implant overdentures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 70 publications
(151 reference statements)
1
17
0
Order By: Relevance
“…As shown by the flow diagram of literature search ( Fig 1 ), a total of 27 studies with 1324 cases and 1808 controls were finally included in meta-analysis [ 22 24 , 26 – 49 ]. There were 10, 3 and 13 studies recruiting patients with IF/IL, MBL and PI, respectively, while Fernandes et al [ 29 ] enrolled participants with various peri-implant disease. Six studies included participants of Asian ancestry while the others included subjects of Caucasian ancestry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by the flow diagram of literature search ( Fig 1 ), a total of 27 studies with 1324 cases and 1808 controls were finally included in meta-analysis [ 22 24 , 26 – 49 ]. There were 10, 3 and 13 studies recruiting patients with IF/IL, MBL and PI, respectively, while Fernandes et al [ 29 ] enrolled participants with various peri-implant disease. Six studies included participants of Asian ancestry while the others included subjects of Caucasian ancestry.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 28 to 369. As to smoking status, 3 studies reported higher smoking rates in peri-implantitis group than healthy implant group [ 28 , 43 , 47 ], 7 enrolled participants matched for smoking status [ 27 , 32 , 33 , 36 , 39 , 40 , 45 ], 9 were performed in non-smokers [ 24 , 26 , 31 , 35 , 37 , 38 , 41 , 44 , 48 ] and 1 in smokers [ 30 ], whereas 7 did not report the smoking status [ 22 , 23 , 29 , 34 , 42 , 46 , 49 ]. IL-1α C-889T polymorphism was investigated in 10 studies, IL-1β C+3954T in 14 studies, IL-1β C-511T in 8 studies, TNFα G-308A in 12 studies, and composite genotype of IL-1α C-889T and IL-1β C+3954T in 7 studies.…”
Section: Resultsmentioning
confidence: 99%
“…The literature supports the evidence that SNPs play an important role in the transcription of these inflammatory mediators and may influence the osseointegration success, including single‐nucleotide polymorphism (SNPs) in MMPs …”
Section: Discussionmentioning
confidence: 57%
“…Some single‐nucleotide polymorphism (SNPs) may affect gene expression levels and protein production or functions; consequently, they influence osteogenesis and inflammatory responses. Some SNPs in cytokines and lipid mediators genes were associated with implant loss and peri‐implantitis, explain some of interindividual risk factors …”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of our study was that it was focused only on single dental implant survival. Articles focused on implants retaining overdentures such as the study by Fernandez et al56 were not included to ensure sample homogeneity and due to a different role that the implant overload factors may play in these cases.…”
Section: Discussionmentioning
confidence: 99%